Profiles of self-care management versus consulting behaviors in adults with heart failure. (1st February 2015) - Lee, Christopher S; Gelow, Jill M; Mudd, James O; Green, Jennifer K; Hiatt, Shirin O; Chien, Christopher; Riegel, Barbara
Abstract: Introduction: Patients with heart failure (HF) vary in their ability to respond to symptoms when they occur. The goal of this study was to classify common patterns of symptom response behaviors among adults with HF and identify biobehavioral determinants thereof. Methods: Consulting behaviors (i.e. contacting a provider for guidance) were measured using the European Heart Failure Self-care Behavior Scale consulting behaviors subscale, and self-care management (i.e. recognizing and engaging in self-initiated treatment of symptoms) was measured with the Self-Care of HF Index self-care management scale in a prospective cohort study. Latent class mixture modeling was used to identify distinct profiles of consulting and of self-care management behaviors. Results: The mean age ( n =146) was 57±13 years, 30% were female, and 59% had class III/IV HF. Two distinct profiles of consulting behaviors (novice and expert) and three distinct profiles of self-care management (novice, inconsistent and expert) were identified. There was a weak association between profiles of consulting behaviors and self-care management (Kendall's tau-b=0.211). Higher levels of anxiety were associated with worse consulting behaviors (β=1.67±0.60) and worse self-care management (β= −5.82±3.12) and lower odds of exhibiting expert level consulting behaviors (odds ratio (OR)=0.50; 95% confidence interval (CI)=0.26–0.95) and self-care management (OR=0.47; 95% CI=0.24–0.92) (all p <0.05). Higher levels of physical symptoms were associated with better self-care management (β=0.50±0.12; OR =1.02, 95% CI=1.00–1.05; both p <0.05). Conclusions: Expertise in consulting behaviors does not necessarily confer expertise in symptom self-care management and vice versa. Physical and psychological symptoms are strong determinants of symptom response behaviors.